FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA DENGAN VARIABEL INTERVENING PERENCANAAN PAJAK SEKTOR PERBANKAN - BAGUS GALUNG RADITYO (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2017)
The purpose of this research is to analyze the factors influencing earnings management, namely company size, leverage, and capital intensity ratio while using tax planning as the intervening variable. Earnings management is the dependent variable in this research. It earnings management is measured by the earnings distribution approach. This research also uses an intervening variable, which is tax planning. The sample in this research consists of 31 banking institutions that are listed on the Indonesian Stock Exchange (Bursa Efek Indonesia) during the period of 2010-2013. The following research employs a quantitative approach by performing a hypothesis test based on the information derived from annual reports and financial statements. The data analysis is performed by using the classic assumption test, path analysis, and hypothesis testing. The outcome of this research shows that company size influence tax planning, tax planning influence earnings management but leverage and capital intensity ratio not influence tax planning,but size, leverage, and capital intensity ratio influence earnings management with tax planning as the intervening variable.